Demand analysis of cayenne chilli pepper in Surakarta City - Aprianti, Feny Andy; Ferichani, Minar; Antriyandarti, Ernoiz (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: This study aims to analyze the factors that affect the cayenne chilli pepper demand, to know its elasticity and to forecast its demand for 2019 up to 2023. Findings: By using time series data of 1993-2017, this study applies multiple regresiion analysis. Methods: The method used for demand foreasting analysis is Least Squares Method and for the error estimator is used Mean Average Deviation. Conclusion: The results show that cayenne chilli pepper price, red chilli pepper price, onion price, the population and income per influence the cayenne chilli pepper demand in Surakarta City. The price elasticity of demand is inelastic and the pruduct categorized as normal goods. Cross elasticity indicates that cayenne chilli pepper subsituted with red chilli with the value of cross elasticity 0,137 and complementered with onion which the value of cross elasticity is -0,094. The result of cayenne chilli pepper demand forecasting for 2019 up to 2023 shows that the potential demand will always increas every year. The value of demand forecast on 2019 is 852.350,24 kg; the value of demand forecast on 2020 is 854.291,99 kg; the value of demand forecast on 2021 is 856.233,74 kg; the value of demand forecast on 2022 is 858.175,49 kg and the value of demand forecast on 2023 is 860. 117,24 kg with the value of error estimator is 0,0048 kg.